THE EFFECT OF WELFARE AND HEALTH ALLOWANCES ON THE WORK PERFORMANCE OF BRI EMPLOYEES OF THE PATI KARABAN UNIT - Nindhita, Yoga; Hendrayanti, Silvia; Wanuri, Wanuri (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2024)
Work performance is a work result achieved by an employee which is seen from his personal characteristics and perception of his role in work, or a separate form of assessment in implementing and improving his work program. This research aims to determine the effect of welfare and health benefits on the work performance of BRI Karaban Pati unit employees. The population in this study were 31 BRI Karaban Pati unit employees. The sampling method used was non-probability sampling with an accidental sampling technique using the census method. The data analysis technique used in this research is multiple regression with the help of calculations via the SPSS application. The results of the calculations that have been carried out show that the t-calculated value of welfare benefits is 2.804 > t-table 2.048. This shows that the welfare benefits variable has a positive and significant effect on employee work performance, so the calculated t value for health benefits is 4.134 > t table 2.048. This shows that the occupational health benefits variable has a positive and significant effect on employee work performance. The coefficient of determination (R Square) is 0.752. This means that the welfare and health benefits variables have a role of 75.2%, together they are able to explain or explain employee work performance variables. It is best for the BRI Karaban unit to distribute bonuses or commissions in the form of performance levels or based on position and responsibility.